Resetting Human Resource Management Seven Essential Steps to Evolve from Crises - Troger, Hermann (Cham : Springer International Publishing : Imprint: Springer, 2022)
In times of globalization, digitalization and demographic change, the COVID-19 pandemic has shown us the fragility and complexity of the world of work. It represents the peak of a process of change in the world of work in economic, social, socio-political and individual psychological terms. This book outlines how effective and future-oriented human resource management can look like in times of demographic and technological change on the one hand and the immediate and lasting effects of the coronavirus pandemic on the other hand. It provides the tools for effective human resource management, summarized in the following seven success factors: demographic-oriented recruitment, strength-oriented workforce deployment, age-appropriate HR development, new generation contract, family and gender, the vital employee, management of interests and expectations. The aim of the book is not only to provide solutions to problems caused by the changing world of work and the pandemic, but also to show how success factors can emerge from these inevitable phenomena. It will be of interest to professionals in the field of human resource management.
Part I. The Baseline -- Chapter 1. Demographic Developments and Other Social Phenomena -- Chapter 2. Impact on the Labor Market -- Part II. Routes to Effective Human Resource Management -- Chapter 3. Demography-oriented Recruitment -- Chapter 4. Strength-based Deployment -- Chapter 5. Age and a Ging Appropriate Development -- Chapter 6. A New Generational Contract -- Chapter 7. Gender Equality and Family -- Chapter 8. Employee Vitality -- Chapter 9. Managing Interests and Expectations -- Part III. Summary and Outlook -- Chapter 10. Summary and Outlook.
Keywords: Personnel management; School management and organization; School administration; Economic sociology; Human Resource Management; Organization and Leadership; Economic Sociology